2022
DOI: 10.3390/endocrines3030029
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin Modulation of Reproductive Function

Abstract: Kisspeptin is a peptide expressed mainly in the infundibular nucleus of the hypothalamus. Kisspeptin plays a crucial role in the regulation of reproductive functions. It is regarded as the most important factor responsible for the control of the hypothalamic–pituitary–gonadal axis, the onset of puberty, and the regulation of menstruation and fertility. Kisspeptin activity influences numerous processes such as steroidogenesis, follicular maturation, ovulation, and ovarian senescence. The identification of kissp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Therefore, LH and FSH signaling is essential for initiating and sustaining spermatogenesis. Specifically, spermatogonia, primary spermatocytes, secondary spermatocytes, and spermatids are arranged in a highly ordered sequence from the basement membrane to the lumen of the seminiferous tubule [43,44]. These germ cell types are associated with spermatogenesis events such as proliferation, differentiation, meiosis, and spermiogenesis, a complex process that transforms round spermatids into complex spermatozoa following meiosis.…”
Section: Spermatogenesismentioning
confidence: 99%
“…Therefore, LH and FSH signaling is essential for initiating and sustaining spermatogenesis. Specifically, spermatogonia, primary spermatocytes, secondary spermatocytes, and spermatids are arranged in a highly ordered sequence from the basement membrane to the lumen of the seminiferous tubule [43,44]. These germ cell types are associated with spermatogenesis events such as proliferation, differentiation, meiosis, and spermiogenesis, a complex process that transforms round spermatids into complex spermatozoa following meiosis.…”
Section: Spermatogenesismentioning
confidence: 99%
“…It is implicated in the regulation of puberty onset, fertility, and pregnancy [36]. Extra hypothalamic Kisspeptin has been found to modulate the secretion of reproductive hormones, influence the development and function of reproductive organs, and participate in the establishment of reproductive behaviors [37,38]. Siminara et al, 2003 have reported that mutation in Kisspeptin receptor knockout (KISS1r −/− or GPR54 −/− ) in mice leads to idiopathic hypogonadotropic hy-pogonadism (small testes in male mice and an absence of follicular maturation in female mice) [39].…”
Section: Introductionmentioning
confidence: 99%
“…It is implicated in the regulation of puberty onset, fertility, and pregnancy [ 36 ]. Extra hypothalamic Kisspeptin has been found to modulate the secretion of reproductive hormones, influence the development and function of reproductive organs, and participate in the establishment of reproductive behaviors [ 37 , 38 ]. Siminara et al, 2003 have reported that mutation in Kisspeptin receptor knockout (KISS1r −/− or GPR54 −/− ) in mice leads to idiopathic hypogonadotropic hypogonadism (small testes in male mice and an absence of follicular maturation in female mice) [ 39 ].…”
Section: Introductionmentioning
confidence: 99%